A new lanthanum(III) complex, [La(MO)3(DMF)3(H2O)2] (MO = methyl orange), and La2O2SO4 nanoparticles; electrocatalytic activity for adsorption/desorption/evolution of hydrogen. (15th October 2015) - Shafaie, Fahimeh; Hadadzadeh, Hassan; Behnamfar, Mohammad Taghi; Amiri Rudbari, Hadi
Graphical abstract: A new lanthanum(III) complex, [La(MO)3 (DMF)3 (H2 O)2 ] (MO − = methyl orange), was synthesized and characterized. The lanthanum oxysulfate nanoparticles (La2 O2 SO4 ) were prepared by calcination of [La(MO)3 (DMF)3 (H2 O)2 ] as a new precursor. The electrocatalytic activity of both compounds for hydrogen adsorption/desorption/evolution reactions of H2 was investigated. Abstract: A new lanthanum(III) complex, [La(MO)3 (DMF)3 (H2 O)2 ] (MO − = methyl orange), was synthesized by the reaction of methyl orange and lanthanum(III) nitrate hexahydrate in the aqueous solution. The complex was characterized by elemental analysis, FT-IR, UV–Vis, and single-crystal X-ray diffraction. Then the lanthanum oxysulfate nanoparticles (La2 O2 SO4 ) were prepared by calcination of [La(MO)3 (DMF)3 (H2 O)2 ] as a new precursor. The nanoparticles were characterized by FT-IR, X-ray diffraction analysis (XRD), and field emission scanning electron microscopy (FE-SEM). Finally, the hydrogen adsorption/desorption properties of the La(III) complex and La2 O2 SO4 nanoparticles were investigated at a glassy carbon electrode (GCE) in H2 SO4 by cyclic voltammetry (CV). The voltammograms showed a pair of peaks corresponding to the adsorption/desorption of hydrogen for both compounds. Also, the electrocatalytic activity of both compounds for the hydrogen adsorption and hydrogen evolution reaction (HER) was investigated by linear sweep voltammetry (LSV).